Völkerkunde zur NS-Zeit aus Wien (1938-1945) Band 1 - Band 3: Institutionen, Biographien und Praktiken in Netzwerken (Verlag der Österreichischen Akademie der Wissenschaften, 2021)
This multi-volume publication with an overall of 42 contributions investigates the position of ,,Völkerkunde" (socio-cultural anthropology) from Vienna during the Nazi era, in exile as well as inside the "Third Reich". Central attention is given to institutional and biographical networks and the history of ideas. The relevant academic spectrum not only includes "Völkerkunde"/ethnology (socio-cultural anthropology), but also comprises important neighboring fields ranging from physical anthropology to archaeological prehistory, folklore studies ("Volkskunde") as weil as to African and Japanese studies.